Pengaruh gezag pendidik terhadap keberhasilan pendidikan agama islam di perguruan tinggi - Sri Haningsih (Islamic University of Indonesia, 2002)
Study of process is never effective to build and develop of whole personal if teacher/lecture as central actor loss their gezag or dignity of educator. It happens because today we have a new paradigm as we called material oriented. To re-actualization the teacher dignity it should be needed: (I) a leading's teacher as best example (uswatun hasanah) perfectly, (2) increasing teacher's salary, could make teacher more confidence about his or her status, (3) supporting from society perfectly.Key Word: The teacher dignity, Islamic Higher education